Flavones 7,8-DHF, Quercetin, and Apigenin Against Tau Toxicity via Activation of TRKB Signaling in ΔK280 TauRD-DsRed SH-SY5Y Cells - Chiang, Ni-Ni; Lin, Te-Hsien; Teng, Yu-Shan; Sun, Ying-Chieh; Chang, Kuo-Hsuan; Lin, Chung-Yin; Hsieh-Li, Hsiu Mei; Su, Ming-Tsan; Chen, Chiung-Mei; Lee-Chen, Guey-Jen (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease with memory loss and cognitive decline. Neurofibrillary tangles (NFTs) formed by hyperphosphorylated Tau protein are one of the pathological hallmarks of several neurodegenerative diseases including AD. Heat shock protein family B (small) member 1 (HSPB1) is a molecular chaperone that promotes the correct folding of other proteins in response to environmental stress. Nuclear factor erythroid 2-like 2 (NRF2), a redox-regulated transcription factor, is the master regulator of the cellular response to excess reactive oxygen species. Tropomyosin-related kinase B (TRKB) is a membrane-bound receptor that, upon binding brain-derived neurotrophic factor (BDNF), phosphorylates itself to initiate downstream signaling for neuronal survival and axonal growth. In this study, four natural flavones such as 7,8-dihydroxyflavone (7,8-DHF), wogonin, quercetin, and apigenin were evaluated for Tau aggregation inhibitory activity and neuroprotection in SH-SY5Y neuroblastoma. Among the tested flavones, 7,8-DHF, quercetin, and apigenin reduced Tau aggregation, oxidative stress, and caspase-1 activity as well as improved neurite outgrowth in SH-SY5Y cells expressing ΔK280 TauRD-DsRed folding reporter. Treatments with 7,8-DHF, quercetin, and apigenin rescued the reduced HSPB1 and NRF2 and activated TRKB-mediated extracellular signal-regulated kinase (ERK) signaling to upregulate cAMP-response element binding protein (CREB) and its downstream antiapoptotic BCL2 apoptosis regulator (BCL2). Knockdown of TRKB attenuated the neuroprotective effects of these three flavones. Our results suggest 7,8-DHF, quercetin, and apigenin targeting HSPB1, NRF2, and TRKB to reduce Tau aggregation and protect cells against Tau neurotoxicity and may provide new treatment strategies for AD.